Enhancing Academic Success in Strawberry Generation: The Influence of Character Education and Social Media on Mental Health - Victorio, Michael; Fauzan, Rizky; Jaya, Arman; Fahruna, Yulyanti (Ilomata International Journal of Management, 2025)
This research examines the direct and indirect effects of Character Education and Social Media Experience on Academic Achievement, mediated by Mental Health. The method used in this study is a quantitative approach, with data collected through questionnaires and analyzed using SEM with the Smart PLS application. The sample size for this study is 200 respondents. The results of this study indicate a significant direct effect of character education and social media experience on academic achievement and an indirect impact of character education on academic achievement through mental health. However, the indirect impact of social media on academic achievement through mental health was not accepted. This research contributes to the improvement of academic achievement among strawberry generation students.